Dermatitis artefacta: self-inflicted genital injury - Olisova OY; Snarskaya ES; Smirnova LM; Grabovskaya O; Anpilogova EM (International Medical Case Reports Journal, 2019)
O Yu Olisova, ES Snarskaya, LM Smirnova, O Grabovskaya, EM Anpilogova Department of Dermatology and Venereology, I.M. Sechenov First Moscow State Medical University (Sechenov University), 119991, Moscow, Russia Background: The term dermatitis artefacta (factitious dermatitis, pathomimia) is reserved for the most severe variant of factitious physical disorder and is characterized by exaggerated lying (pseudologia fantastica), sociopathy, geographic wandering (peregrinating) from hospital to hospital, and seeking to be in the patient role.Objective: This report aims to give attention to the importance of accurate and detailed history, and conducting an appropriate physical examination in patients with life-threatening diseases when the underlying cause is not apparent. The diagnosis of dermatitis artefacta must always be upheld.Case presentation: We present a unique case of a 52-year-old male who presented to clinic with skin lesions on scrotum and shaft of his penis and that were very distinct and suggestive of pyoderma gangrenosum which he developed 3 months after previous discharge from the clinic. Clinical response to treatment and the absence of laboratory findings confirmed a dermatitis artefacta.Conclusion: Dermatitis artefacta is a factitious disorder that involves falsification of psychological or physical signs or symptoms caused entirely by the patients themselves, in a clear state of consciousness, in order to play the role of a sick person. The correlation of anamnestic data and clinical and para-clinical exams was essential for the diagnosis of dermatitis artefacta in this case. To the best of our knowledge, pyoderma gangrenosum-like lesions have never been reported in a patient with dermatitis artefacta. Herein, we describe a rare case report of self-inflicted genital injury in a 52-year-old male. Keywords: factitious dermatitis, dermatitis artefacta, pathomimia, schizophrenia, pyoderma gangrenosum, contact dermatitis, herpes simplex, psoriasis